Sarcopenia: A review - O P Gupta (Wolters Kluwer Medknow Publications, 2020)
Sarcopenia is the process of loss of skeletal muscle mass. It has recently been recognized as a separate entity, and there is very little awareness about it among health professionals. Sarcopenia is a geriatric condition where there is an age-related primary loss of muscle mass, although it has now been recognized to begin early in life. In general, loss of muscle mass occurs secondary to chronic illness, malignancy, or drugs, particularly long-term steroid therapy and cytotoxic drugs. Aging itself may cause sarcopenia, especially in inactive individuals who have a sedentary lifestyle. There is a decrease in muscle mass with increase in intra- and intermuscular adipose tissue. Besides epigenetic factors, malnutrition, chronic inflammation (raised cytokine levels of interleukin (IL)-1, IL-6, and tumor necrosis factor-alpha), and changes at hormonal and mitochondrial level are responsible for the poor muscle growth and loss of muscle mass and strength and thereby affect the performance of activities of daily living. Diagnosis of sarcopenia can be made by simple clinical tests which detect loss of muscle mass and strength. Loss of muscle mass can be confirmed with the help of computed tomography, magnetic resonance imaging, and ultrasonography. Exercise and improvement of nutrition are the mainstays of treatment. So far, no specific drug is available for the treatment of sarcopenia, though some age-old drugs such as metformin and anabolic steroids have been tried with variable results. Some new molecules have shown positive results in experimental animals and are in various phases of clinical trials.